A novel fire prevention and control plastogel to inhibit spontaneous combustion of coal: Its characteristics and engineering applications. (1st March 2020) - Fan, Yi-Jin; Zhao, Yan-Yun; Hu, Xiang-Ming; Wu, Ming-Yue; Xue, Di
Highlights: Plastogel combine the advantages of sodium silicate gel and organic polymer gel. The gelation time is short and generally within 2 min. This paper introduces the concrete application method of plastogel. The plastogel have been used in practical engineering, which achieved good results. Abstract: In order to address the issue of spontaneous combustion in coal mines during the mining process, we have proposed a novel plastogel which can prevent and control fires in coal mines. The novel plastogel was prepared by introducing a polymer plasticizer into the conventional water glass gel (water glass/coagulant/bentonite system). The effect of different concentrations of components on the properties of plastogel was analyzed by testing the gelation time and water retention of the plastogel. The Infrared spectroscopy results indicate that plastogel can effectively inhibit the oxidation of methylene in the coal body. The SEM results illustrated that the surface morphology of the plastogel and conventional water glass gels were significantly different. The compactness and smoothness of the plastogel were significantly enhanced after the addition of plasticizer. The results of the on-site application of plastogel in the withdrawal of 1308 working face of Shandong Longyun Coal Industry Co., Ltd. suggest that the plastogel effectively inhibited the oxidation of the crushed coal body, significantly reduced the temperature of coal body, and ensured a safe withdrawal of rack on the working face. The formulated plastogel had distinct practical advantages and is proposed as an ideal fire prevention and control material.